Efektivitas Penggunaan E-Filing dan E-Form Terhadap Pelaporan SPT Tahunan Orang Pribadi di Kantor Konsultan Pajak (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study examines the advantages and disadvantages of reporting Annual Tax Returns (SPT) at tax consultant offices using e-filing and e-form. The method used is descriptive qualitative approach, data were collected through direct interviews with tax consultant office owners in Sidoarjo. The study findings indicate that although e-filing and e-form offer accuracy, efficiency, and simplicity in tax submission, there are a number of weaknesses, including lack of taxpayer understanding, slow coordination, and difficulty adjusting to system modifications. Because e-form can be filled in gradually and contains automatic filling options based on data from previous years, it is considered more flexible and appropriate for use by tax experts. This study recommends improving education for taxpayers and developing a more responsive and easy-to-use system to support the digitalization of taxation in Indonesia.